The Impact of Industrialization, Renewable Energy, Energy Consumption and Financial Development on CO2 Emissions in the Framework of the Environmental Kuznets Curve - Efeoğlu, Rabia (Alanya Alaaddin Keykubat Üniversitesi, 2021)
In the study, the effect of industrialization, renewable energy, energy consumption and financial development on CO2 emissions in E7 countries during the 1989-2016 period was examined within the framework of the Environmental Kuznets Curve hypothesis. In the study in which the panel data method was used, the fixed effects model was preferred and the model was estimated with the Parks-Kmenta Estimator. As a result of the study, it has been found that GDP per capita, industrialization and energy consumption increase CO2 emissions in E7 countries, GDP per capita squared, renewable energy and financial development reduce CO2 emissions, and within this framework, the EKC hypothesis is valid.

Çalışmada E7 ülkelerinde 1989-2016 döneminde sanayileşme, yenilenebilir enerji, enerji tüketimi ve finansal gelişmenin CO2 salınımı üzerindeki etkisi Çevresel Kuznets Eğrisi hipotezi çerçevesinde incelenmiştir. Panel veri yönteminin kullanıldığı çalışmada sabit etkiler modeli tercih edilerek Parks-Kmenta Tahmincisi ile model tahmin edilmiştir. Çalışmanın sonucunda E7 ülkelerinde kişi başına GSYH, sanayileşme ve enerji tüketiminin CO2 emisyonunu artırdığı, kişi başına GSYH karesi, yenilenebilir enerji ve finansal gelişmenin CO2 emisyonunu azalttığı ve bu çerçevede ÇKE hipotezinin geçerli olduğu bulgusuna ulaşılmıştır.
Keywords: Environmental Kuznets Curve; Industrialization; Renewable Energy; Financial Development; Economics; Ekonomi; Çevresel Kuznets Eğrisi; Sanayileşme; Yenilenebilir Enerji; Finansal Gelişme